Recurrent disseminated Mycobacterium avium in a female patient from Thailand with anti-interferon-gamma autoantibodies: dilemma on treatment approach. Issue 1 (28th January 2021) - Zeitler, Kristen; Walter, Jolan; Khan, Fatima; Sriaroon, Chakrapol
Abstract : Anti-interferon-gamma (IFN-γ) autoantibodies has been recognised as an adult-onset immunodeficiency in the past decade in people who originate from Southeast Asia. These patients are susceptible to particular opportunistic infections, especially non-tuberculous mycobacteria (NTM). We present the case of a woman whom originally came from Thailand with disseminated Mycobacterium avium complex infection (pleural, pericardium, bloodstream and lung parenchymal involvement). Her infection continued to progress while receiving proper antibiotic treatment. Once high titre neutralising anti-IFN-γ autoantibodies were detected, rituximab was added as adjunctive treatment. The patient had remarkable clinical improvement against persistence of anti-IFN-γ autoantibodies. Although her lung disease has improved, the patient continues on triple therapy for NTM. The kinetics of anti-IFN-γ autoantibodies in the context of clinical progression, indication and length for rituximab and triple therapy is discussed in view of the current literature.